Alterations of B Cells in Immunosuppressive Phase of Septic Shock Patients*. Issue 6 (June 2020) - Dong, Xijie; Liu, Qinxin; Zheng, Qiang; Liu, Xinghua; Wang, Yuchang; Xie, Zhenxing; Liu, Tao; Yang, Fan; Gao, Wei; Bai, Xiangjun; Li, Zhanfei
Abstract : Objectives: Septic shock is a subset of sepsis related to acute circulatory failure characterized by severe immunosuppression and high mortality. Current knowledge about B-cell status in the immunosuppressive phase of septic shock is sparse. The aim of this study was to investigate the alterations of B Cells in the immunosuppressive phase of septic shock. Design: Prospective cohort study. Setting: Adult ICUs at a university hospital. Patients: Adult septic shock patients without any documented immune comorbidity. Interventions: None. Measurements and Main Results: The absolute counts of lymphocytes and B cells of 81 patients and 13 healthy controls, and serum immunoglobulin levels of 64 patients and 10 healthy controls were determined by clinical laboratory. The percentages and counts of B-cell subsets of 33 patients and 10 healthy controls and the immunoglobulin M expression on B-cell subsets of 20 patients and five healthy controls were quantified by flow cytometry. Immunoglobulin levels produced by B cells after stimulation in vitro of 20 patients and five healthy controls were tested by enzyme-linked immunosorbent assay. Redistribution and selective depletion of B-cell subsets in septic shock patients were discovered, and a decrease in immunoglobulin M levels was associated with a reduction in resting memory B-cell counts. These alterations were more pronounced in nonsurvivors compared with survivors. Additionally, receiver operating characteristic curve analysis showed that the data of B-cell subsets had the best predictive value for mortality risk. Conclusions: Severe B-cell abnormalities are present in the immunosuppressive phase of septic shock and are associated with prognosis. Abstract : Supplemental Digital Content is available in the text.